The Rupturing of Samoa’s Foundations: On the Importance of a Public Theology - Sam Amosa (Religions)
The Samoan general election of 2021 provoked an unprecedented constitutional crisis. It represented yet one more symptom in a shaking of the foundations—not just in politics but within the very nature of Samoan society. The nation’s past stability had resided in the cultural virtue of respect, which permeated its key pillars—the church, law and fa’a Samoa (the customary Samoan way of life). There had been several tremors prior to the election. These had involved court cases involving the church where the Congregational Christian Church Samoa was shown to be in the wrong. These tremors and the more substantial shaking brought about by the constitutional crisis pose several awkward questions as regards the way in which the Christian faith and the Samoan cultural way of life–fa’a Samoa—are commonly regarded as more than complimentary. They also call into question the church’s default practice of silence in the face of public issues. Is it now time to nurture and encourage the public role of the faifeau (minister) for the sake of the common good in a time of significant change? In the absence of a prophetic theology, the tremors and shaking of the foundations signify the necessity of taking some further steps in the development of a local public theology.